2012
DOI: 10.1186/1471-230x-12-69
|View full text |Cite
|
Sign up to set email alerts
|

A low level of serum total testosterone is independently associated with nonalcoholic fatty liver disease

Abstract: BackgroundThe association between low serum testosterone levels, visceral adipose tissue (VAT), and metabolic syndrome is now well known. However, the relationship between hepatic steatosis and serum testosterone levels has not been extensively studied. Our aim was to investigate the association of serum total testosterone levels with nonalcoholic fatty liver disease (NAFLD), adjusting for the influence of VAT and insulin resistance.MethodsThis study is a retrospective observational cross-sectional one of heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
111
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(122 citation statements)
references
References 44 publications
8
111
0
3
Order By: Relevance
“…Second, it is well accepted that prostate cancer is a testosterone-dependent malignancy. Recent observational studies have showed that a low serum total testosterone level is independently associated with NAFLD regardless of visceral adipose tissue and insulin resistance (Völzke et al 2010, Kim et al 2012. In our study, consistent with previous findings, we could measure serum testosterone in 76 patients (28 patients with NAFLD and 48 patients without NAFLD) after excluding patients treated with androgen deprivation therapy (ADT).…”
Section: Discussionsupporting
confidence: 79%
“…Second, it is well accepted that prostate cancer is a testosterone-dependent malignancy. Recent observational studies have showed that a low serum total testosterone level is independently associated with NAFLD regardless of visceral adipose tissue and insulin resistance (Völzke et al 2010, Kim et al 2012. In our study, consistent with previous findings, we could measure serum testosterone in 76 patients (28 patients with NAFLD and 48 patients without NAFLD) after excluding patients treated with androgen deprivation therapy (ADT).…”
Section: Discussionsupporting
confidence: 79%
“…Both reported reductions in metabolic syndrome but were of longer duration (1-2 years) and both specifically recruited men with metabolic syndrome. However, no studies thus far have targeted reversal of NAFLD despite an independent association between low testosterone levels and hepatic steatosis, a marker for NAFLD (60,61). The prevalence of NAFLD is increasing, particularly in patients with cardiometabolic risk factors and is associated with increased risk of liver damage and possibly future CVD (52,62).…”
Section: Discussionmentioning
confidence: 99%
“…Both human and rodent studies provide evidence for a protective effect of estrogen and testosterone on the development of fatty liver (15)(16)(17)(19)(20)(21). We set out to investigate the effect of gonadectomy in three different strains of both sexes.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that breast cancer patients treated with an estrogen receptor antagonist develop massive hepatic steatosis and even typical NASH indicates that estrogen affects development of this disease (16). Cross-sectional studies assessing the association between plasma testosterone and NAFLD have shown conflicting results (17)(18)(19). However, rodent studies have shown that both estrogen and testosterone can have an inhibitory effect on liver lipid accumulation (20,21).…”
Section: Accession Numbersmentioning
confidence: 99%